1990
DOI: 10.2105/ajph.80.6.722
|View full text |Cite
|
Sign up to set email alerts
|

Cervix and breast cancer incidence in immigrant Caribbean women.

Abstract: Cervix and breast cancer incidence in 1978-82 was computed for immigrant and United States-born Black women in Brooklyn, New York. Compared to the national SEER (Surveillance, Epidemiology and End Results) rates, US-born and Haitian women had high rates of invasive cervical cancer, while Englishspeaking Caribbean immigrants had an average rate. However, while US-born women had an average rate of carcinoma in situ of the cervix, both immigrant groups had low rates. Both immigrant groups had low rates of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
(2 reference statements)
1
12
0
Order By: Relevance
“…In contrast, the impact of nativity on breast cancer incidence and mortality also has been explored. 3,[21][22][23][24][25] Specifically, studies focusing on nativity and incidence of breast cancer concluded that U.S.-blacks have higher incidence rates compared to foreign blacks. 23 Moreover, breast cancer mortality studies indicated that foreign-born blacks fair better than U.S.-born blacks, and that foreign-born blacks have similar mortality rates as whites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the impact of nativity on breast cancer incidence and mortality also has been explored. 3,[21][22][23][24][25] Specifically, studies focusing on nativity and incidence of breast cancer concluded that U.S.-blacks have higher incidence rates compared to foreign blacks. 23 Moreover, breast cancer mortality studies indicated that foreign-born blacks fair better than U.S.-born blacks, and that foreign-born blacks have similar mortality rates as whites.…”
Section: Discussionmentioning
confidence: 99%
“…3,[21][22][23][24][25] Specifically, studies focusing on nativity and incidence of breast cancer concluded that U.S.-blacks have higher incidence rates compared to foreign blacks. 23 Moreover, breast cancer mortality studies indicated that foreign-born blacks fair better than U.S.-born blacks, and that foreign-born blacks have similar mortality rates as whites. 26 However, neither of these studies explored the role of breast cancer risk factors on the observed difference in incidence and mortality according to nativity status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consedine et al found that Haitian men reported significantly lower prostate cancer screening compared with U.S. born whites [3]. Haitian women have been found to be less likely to utilize breast cancer screening [4,5], and have lower Papanicolaou (Pap) test screening rates than native-born Black and Latina peers [6], and a higher incidence of invasive cervical cancer than U.S.-born black women [7]. Regardless of ethnicity or socioeconomic status, increasing cancer screening results in early detection of many cancer types, lowers incidence of late stage cancer diagnosis, and improves cancer outcomes, considerably enhancing survival rates [8].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that US-born Black women and Haitian women had higher rates of cervical cancer than West Indian women, but both West Indian and Haitian immigrant women had lower rates of breast cancer than US-born Black women. 17 Similarly, national data from the Commonwealth Minority Health Survey indicated that Blacks of Caribbean ancestry had higher levels of stress, especially financial stress, and higher levels of psychological symptoms than US-born Blacks. 18 Given the relatively small number of Caribbean immigrants in the sample, these data have important limitations; however, they highlight the importance of paying attention to the diversity of the Black population.…”
Section: We Need To Assess the Diversity Of The Black Populationmentioning
confidence: 99%